Potensi Antiproliferasi Jintan Hitam (Nigella sativa) pada Sel Lambung Tikus yang Diinduksi 7,12-Dimetil Benzena Anthrasena (ANTIPROLIFERATION EFFECTS OF NIGELLA SATIVA IN GASTRIC CELL RATS INDUCED 7,12-DIMETHYL BENZ (A) ANTHRACENE) - Farihah, Rizky; Baroroh, Hanif Nasiatul; Ekowati, Heny (Jurnal Veteriner, 2013)
Studies have been conducted to determine the potential antiproliferative effect of Nigella sativa seed(NSS) extract on 7,12- dimetilbenza[a]antrasena (DMBA)-induced female rats. The chloroform NSS extracteffect was observed on rat gatric cells. Sprague Dawley  female rats were divided into five groups, eachgroup consisted of 12 individuals. A control group was DMBA, Groups B, C and D were the groups treatedwith NSS extract with ranked dose 250 mg / kg, 500 mg / kg and 750 mg / kg and group E is the corn oilcontrol group. Histopathological observation of cells using H&E staining and cell proliferation activity wasobserved with the mean AgNOR (mAgNOR). mAgNOR values   were analyzed using Kolmogorov-Smirnovtest, than followed with ANOVA one way, and Tukey test HSD. The results showed H&E staining and  thechloroform exctract showed mAgNOR N.sativa semen were able to reduced gastric cell damage and lowergastric cell proliferation in DMBA- induced rat. The results showed that N.sativa potential to develop asa chemopreventive agent in gastric cancer.
Keywords: Nigella sativa, antiproliferation, gastric cancer, 7,12-dimethyl benz(a) anthracene (DMBA)